Goal-oriented incentive payment in CUDAM institution and variation in medical visit indicators in children under one and pregnant women - Marcelo Morales; Jorge Fernandez (Medwave, 2011)
ntroduction: The establishment of National Integrated Health System in Uruguay from 2007 led to changes in the financing of the Collective Health Care Institutions (IAMC). They charge the National Health Fund (FONASA) for their partners from social security (SS) a health fee consists of: a) A risk-adjusted capita (94%)b) A component for compliance with performance (6%), depending on the fulfillment of three goals of care. Goal 1 is a component of the child under 1 year and a component of the pregnant woman. For both components were established institutional baseline (July 2007-September 2008) in the control patients in both age groups. This motif COMPLIANCE quarterly reports with a fee of $48/user FONASA/month for average baseline compliment. Las for children and pregnant women were monitored for IAMC CUDAM 64% and 59% respectively.This institution has 42,000 users, 95% derived from SS, featuring 45 births, 585 children <1 year and 405 pregnant women tested monthly.Objectives: Evaluate two years (July-September 2010):a) The mean percentages of compliance for children and pregnant CUDAM with medical controlb) Relationship between income through the FONASA insitucional for goal 1 and children and pregnant women in medical management during the quarter.Methods: a retrospective study of children and pregnant women with medical control CUDAM. In turn, each target has 6 indicators (N: children, F: females). Child: N1 and N2: derivation and acquisition of the newborn, N3: controls as a guideline, N4: current vaccination, N5: ultrasound hip and pregnant, N6: accreditation in good feeding practices for infants and young children and pregnant women. Pregnant woman: M1 controls as a guideline, M2: leaf perinatal information system, M3: HIV and VDRL performed, M4: uptake in 1 st quarter, M5 and M6: dental checkup during pregnancy and postpartum.Results: The mean percentages of compliance for children and pregnant women increased to 92% (164 additional children) and 88% (117 additional pregnant) respectively. Insitucional monthly income for the goal 1 was $1,915,200 (US$1 = $20).Average income/month was $1,637 and $2,364 per child and pregnant women respectively. We conclude that the target incentive payment of 1 allowed to significantly improve the indicators of child and maternal control of CUDAM.